Irrigated agriculture for food self-sufficiency in the sub-Saharan African region - Darko, Ransford Opoku; Liu, Junping; Yuan, Shouqi; Sam-Amoah, Livingstone K; Yan, Haofang (International Journal of Agricultural and Biological Engineering, 2020)
Increasing agricultural productivity in Africa will have important impacts not only on the agricultural sector but also can be a catalyst for industrialization through agro-processing. Irrigation, therefore, has a crucial role in enhancing food security and reducing hunger in the region. Numerous countries in Africa consider water and irrigation management as a key factor in improving their food security and ensuring access to drinking-water for their populations. Fortunately, there is evidence from a number of places on the continent where the adoption of efficient irrigation systems has led to higher productivity among smallholder farmers. While the appropriate interventions for the diverse agro-ecological zones of sub-Saharan Africa are known, adoption among smallholder farmers still remains a challenge. Digital technology opens the vast untapped potential for farmers, investors, and entrepreneurs to improve the efficiency of food production and consumption in Africa. From precision farming to an efficient food supply chain, technology could bring major economic, social, and environmental benefits. Increasing investment and involvement of the private sector is crucial for the up-scaling of irrigation technologies. Indeed, the sheer optimism across the startup ecosystem is that extreme hunger can be cured in Africa, in this generation, by significantly transforming the industry that employs most of its citizens. This paper draws on lessons from past trends in the irrigation industry and emphasizes on novel directions to ensure that farmers, as well as other stakeholders reap the benefits associated with improved technologies. Keywords: food self-sufficiency, irrigation development, small-holder farms, sub-Sahara Africa, sustainability DOI: 10.25165/j.ijabe.20201303.4397 Citation: Darko R O, Liu J P, Yuan S Q, Sam-Amoah L K, Yan H F. Irrigated agriculture for food self-sufficiency in the sub-Saharan African region. Int J Agric & Biol Eng, 2020; 13(3): 1–12.